Philosophy, film, and the dark side of interdependence - Beever, Jonathan, 1980- (Lexington Books, 2020)
"Why might interdependence, the idea that we are made up of our relations, be horrifying? Philosophy, Film, and the Dark Side of Interdependence argues that philosophy can outline the contours of the dark spectre, and that film can shine a light on its shadowy details, together revealing a horror of relations"--